Phase 1 Safety and Immunogenicity Study of a Respiratory Syncytial Virus Vaccine With an Adenovirus 26 Vector Encoding Prefusion F (Ad26.RSV.preF) in Adults Aged ≥60 Years. (22nd April 2020) - Williams, Kristi; Bastian, Arangassery Rosemary; Feldman, Robert Allen; Omoruyi, Edmund; de Paepe, Els; Hendriks, Jenny; van Zeeburg, Hester; Godeaux, Olivier; Langedijk, Johannes P M; Schuitemaker, Hanneke; Sadoff, Jerry; Callendret, Benoit
Abstract: Background: Despite the high disease burden of respiratory syncytial virus (RSV) in older adults, there is no approved vaccine. We evaluated the experimental RSV vaccine, Ad26.RSV.preF, a replication-incompetent adenovirus 26 vector encoding the F protein stabilized in prefusion conformation. Methods: This phase 1 clinical trial was performed in healthy adults aged ≥60 years. Seventy-two participants received 1 or 2 intramuscular injections of low-dose (LD; 5 × 10 10 vector particles) or high-dose (HD; 1 × 10 11 vector particles) Ad26.RSV.preF vaccine or placebo, with approximately 12 months between doses and 2-year follow-up for safety and immunogenicity outcomes. Results: Solicited adverse events were reported by 44% of vaccine recipients and were transient and mild or moderate in intensity. No serious adverse events were related to vaccination. After the first vaccination, geometric mean titers for RSV-A2 neutralization increased from baseline (432 for LD and 512 for HD vaccine) to day 29 (1031 for LD and 1617 for HD). Pre-F–specific antibody geometric mean titers and median frequencies of F-specific interferon γ–secreting T cells also increased substantially from baseline. These immune responses were still maintained above baseline levels 2 years after immunization and could be boosted with a second immunization at 1 year. Conclusions: Ad26.RSV.preF (LD and HD) had an acceptable safety profile and elicited sustained humoral and cellular immune responses after a single immunization in older adults. Abstract : The Ad26.RSV.preF vaccine was well tolerated, had an acceptable safety profile, and was immunogenic after a single dose. The response to the vaccine seems to persist for ≥2 years and was recallable.